Implications of cortical structure and connectivity in autism spectrum disorder - Fitzgerald, Jacqueline (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2015)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterised by early-onset deficits in social communication and interaction together with recurrent restricted repetitive behaviours (APA, 2013). Insights from genetic, neuropathological and neuroimaging studies has led to the emergence of the 'altered cortical connectivity' theory of ASD (Casanova and Trippe, 2009, Courchesne and Pierce, 2005a, Just et al., 2004, Kana et al., 2007, Gilman et al., 2011) which suggests that the social, cognitive and behavioural deficits characteristic of ASD are underpinned by disrupted connectivity between distinct neural regions.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin